Biowaste and by-products as rearing substrates for black soldier fly ( Hermetia illucens ) larvae: Effects on larval body composition and performance - Eggink, Kylian Manon; Lund, Ivar; Pedersen, Per Bovbjerg; Hansen, Benni Winding; Dalsgaard, Johanne (PLOS ONE, 2022)
Black soldier fly ( Hermetia illucens ) larvae can convert biowaste and by-products into body mass high in protein (~40% dry matter, DM) and lipid (~30% DM). However, the type of rearing substrate also affects the larval body composition and thus its nutritional value. Hitherto, it remains unclear how and to what extent the larval body composition can be altered by the substrate. This study was therefore performed to examine the possibilities of modifying larval body composition using different rearing substrates. To investigate this, 5-days old larvae were reared for seven days on different locally available waste and by-products: brewer’s spent grain, mitigation mussels ( Mytilus edulis ), rapeseed cake, and shrimp waste meal ( Pandalus borealis ). Larval composition and performance were compared to larvae reared on a commercial chicken feed as well as a mixed feed (mixture of chicken feed and by-products, with a similar macronutrient composition to chicken feed). Larval body weight was recorded daily to determine growth over time whereas larvae and substrates were sampled at the start and end of the trial and analysed for their nutritional composition. The type of rearing substrate affected both larval body composition and growth performance. There was a clear relation between the nutritional composition of the substrate and larvae for certain fatty acids. Larvae reared on marine-based waste substrates contained a higher share of omega-3 fatty acids than larvae reared on the other substrates, indicating an accumulation of omega-3 fatty acids from the substrate. There was a strong positive linear correlation between the ash content in the substrate and larvae whereas larval lipid, protein, amino acid, and chitin content seemed more affected by larval development. Overall, this study showed that the rearing substrate affects larval composition and development, and that larval composition of certain nutrients can be tailored depending on further food and feed applications.